2016
DOI: 10.1371/journal.pone.0166620
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Community-Based Sodium Reduction Program in Rural China – A Cluster-Randomized Trial

Abstract: BackgroundAverage sodium intake and stroke mortality in northern China are both among the highest in the world. An effective, low-cost strategy to reduce sodium intake in this population is urgently needed.ObjectiveWe sought to determine the effects of a community-based sodium reduction program on salt consumption in rural northern China.DesignThis study was a cluster-randomized trial done over 18 months in 120 townships (one village from each township) from five provinces. Sixty control villages were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(114 citation statements)
references
References 24 publications
3
99
0
Order By: Relevance
“…Of the two studies using 24-hour urinary sodium as an outcome measurement method, one had a more scientifically robust design: a cluster RCT by Li and colleagues. 17 This study reliably reports a statistically significant decrease in salt intake among the study population and provides encouraging evidence that community-based health education in addition to a low-sodium salt substitute are effective in reducing dietary salt consumption.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Of the two studies using 24-hour urinary sodium as an outcome measurement method, one had a more scientifically robust design: a cluster RCT by Li and colleagues. 17 This study reliably reports a statistically significant decrease in salt intake among the study population and provides encouraging evidence that community-based health education in addition to a low-sodium salt substitute are effective in reducing dietary salt consumption.…”
Section: Discussionsupporting
confidence: 55%
“…Four of seven studies showed statistically significant decreases in the dietary salt intakes of study populations as a result of behavior interventions: one large repeated cross-sectional population study, 15 two small community-based studies (one that provided nutritional counseling in a University setting 16 and another that provided cooking classes in a rural setting), and one large cluster randomized trial including a salt substitute combined with consumer education intervention. 17 Of the remaining three studies, one found statistically significant decreases in mean sodium density of packaged food products following a national salt reduction initiative for voluntary, category-specific sodium targets for packaged food. The other two studies found significant improvements in nutrition behaviors relating to salt intake after consumer education in a pilot study 18 and a community-based RCT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, evidence from the cluster RCT in rural China where potassium salts were provided to 60 villages produced statistically but not clinically significant reductions in sodium intake (mean reduction of sodium intake was 14 mmol per day). 5 There is also emerging evidence that salt reduction strategies are most effective when targeted to those in the highest quartile of intake and not the general population. 6 Second, the statement by the authors that "use of salt substitutes as a public health intervention warrants consideration as part of policy recommendations" is of great concern to us.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Although a systematic review and meta‐analysis of clinical studies have demonstrated blood pressure lowering effects of reduced‐sodium, added‐potassium salt substitutes, 16 such studies have to date mostly been conducted in China 17‐20 . Given the high prevalence of excess sodium intake in India, the current study set out to test the effect of salt substitute on BP among hypertensive patients in India.…”
Section: Introductionmentioning
confidence: 99%